2018
DOI: 10.4018/978-1-5225-3041-1.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of an Instructional Program for Teaching Programming Processes to Gifted Students Using Scratch

Abstract: This chapter examines practical applications of an educational program designed to teach Turkish gifted second, third, and fourth grade students programming using Scratch, an online programming website (https://scratch.mit.edu). This qualitative research study was conducted with gifted identified students in an elementary school in Ankara's Altındağ district. Qualitative data collection methods were used. The study found program strengths included practical orientation, student independence, student free expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Programming education in K–12 is a topic that gets more and more important day by day. It is possible to see the reflection of this importance in the policies of many countries (Durak, ). Because programming education is necessary for the acquisition and development of qualifications of the 21st century (Fessakis, Gouli, & Mavroudi, ; Kalelioğlu & Gülbahar, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programming education in K–12 is a topic that gets more and more important day by day. It is possible to see the reflection of this importance in the policies of many countries (Durak, ). Because programming education is necessary for the acquisition and development of qualifications of the 21st century (Fessakis, Gouli, & Mavroudi, ; Kalelioğlu & Gülbahar, ).…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, according to the understanding of education framework of the 21st century, it is expected that students should be able to form a specific product, present the product, express themselves creatively, and present their knowledge in a productive manner (Kırmacı & Yıldırım, ). Hence, it can be concluded that the programming skill has turned into the basic skill of the 21st century (Durak, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Mazman (), as programming is a skill that an individual possesses, it is not used only for short‐term purposes, yet it is possible to transfer it to problem‐solving, presenting a product and other situations when it is necessary. It is important in terms of improving communication programming skills in the process of education (Durak, ). Communication of students in FC, both in class and out‐of‐class with their peers and teachers should be encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen‐week programming course was carried out in the FC model with the students in the 5th, 6th, 7th, and 8th years of middle school. Scratch program was chosen as a programming teaching tool because Scratch is the most commonly used and most functional tool in early programming teaching (Durak, ). In addition, the use of Scratch positively influences children's learning to program and engagement in teaching programming (Zuckerman, Blau, & Monroy‐Hernández, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation